(untitled) (CIPEEX, 2025)
Introduction: Exosomes are extracellular vesicles produced by several cells, specifically, those derived from stem cells, they are used in skin regeneration applications. Exosomes act on cell renewal through the growth factors of nearby epithelial cells. Thus, exosomes are a promising strategy in advanced aesthetics, with the potential to promote tissue repair and delay skin aging. Objective: To conduct a bibliographic study on the use of exosomes in facial treatments, highlighting their responsibilities and importance during aesthetic procedures. Methodology: A narrative literature search was carried out in August 2025, using the following keywords: Exosomes (AND); (AND) Facial treatments (OR) Aesthetics. The searches were carried out in the PubMed database, including complete scientific articles published in Portuguese and English, which addressed the professional performance in facial treatments. Results: The results indicate that exosomes derived from stem cells promote multiple regenerative effects on the skin: marked cell proliferation and resistance to oxidative stress, as well as acceleration of healing and improvement of fibroblast function. Specifically, exosomes containing the lncRNA MALAT1 accelerate regeneration based on activation of the miR-378a/FGF2 axis. In addition, exosomes from adipose-derived stem cells have been shown to be effective in improving the healing of cutaneous wounds. Conclusion: Exosomes show great potential in facial treatments, promoting cell regeneration, healing and improving fibroblast function. Its application represents an innovative and less invasive strategy in advanced aesthetics. It is important to carry out more clinical studies to consolidate safe and standardized protocols. KEYWORDS: Tissue Repair. Aesthetics. Skin Regeneration. Facial Treatments.